Borrelia burgdorferi disrupts gut barrier functions and microbiota–antibody interactions - Shilpa Sachan; Giang Vu Vi Tran; Kimberly J. Olsen; Heather Kulaga; Anne Day; Hannah P. Savage; Alison W. Rebman; John N. Aucott; Isabel A. Jimenez; Cory F. Brayton; Nicole Baumgarth (Journal of Experimental Medicine, 2026)
Lyme disease, an emerging tickborne disease caused by Borrelia burgdorferi (Bb), can result in myriad symptoms of unknown causes in humans. Here, we show that Bb rapidly disrupts the gastrointestinal immune barrier in infected mice, inducing a “leaky gut” syndrome, characterized by increased gut permeability, systemic endotoxemia, elevated LPS binding protein and intestinal fatty acid binding protein, and altered blood leukocyte profiles. Patients with acute Lyme disease showed similar blood changes that correlated with disease symptoms and liver function measurements and largely resolved after antibiotic treatment. Mechanistically, Bb infection triggered mild early inflammation in the small intestine and suppressed humoral immunity to the microbiota, resulting in reduced IgA coating of fecal microbes and decreased antimicrobial serum IgG, despite the increased gut permeability. These defects preceded shifts in later observed gut bacterial composition and short-chain fatty acid production. Together, our findings identify mucosal barrier dysfunction and impaired antimicrobial humoral immunity as potential drivers of Bb-induced disease.